Sistem Informasi Perhitungan Harga Pokok Produksi UD Kerupuk Rengganis - Widiyanto, Dhika (Jurnal Ekonomi dan Teknik Informatika, 2024)
UD Kerupuk Rengganis is a medium-sized small business located in Bandung Rejo Village Rt 02 Rw 01 Bayan sub-district. At present UD Kerupuk Rengganis is still calculating the cost of production using traditional costing systems. The traditional cost system is the costs associated with the production process, which is relatively low, not counted all. For example, the factory overhead costs (electricity and water costs), so the cost of production determined is not right. Based on the description above, in this study an information system for calculating the cost of production of UD Kerupuk Rengganis will be made. The author carries out data collection techniques obtained using literature study techniques, interviews, and observations. The system design used is web-based, which can facilitate adding, deleting, printing production data, and making reports more effective and efficient, such as simplifying data searches so as not to spend a lot of time. The purpose of writing this is to apply the Production Cost Calculation Information System for UD Kerupuk Rengganis.